Growth patterns of monochorionic twin pregnancy complicated by Type‐III selective fetal growth restriction. (3rd March 2022) - Shinar, S.; Xing, W.; Lewi, L.; Slaghekke, F.; Yinon, Y.; Raio, L.; Baud, D.; DeKoninck, P.; Melamed, N.; Huszti, E.; Sun, L.; Van Mieghem, T.; et al.
ABSTRACT: Objectives: Little is known regarding fetal growth patterns in monochorionic twin pregnancy complicated by Type‐III selective fetal growth restriction (sFGR). We aimed to assess fetal growth and umbilical artery Doppler pattern in Type‐III sFGR across gestation and evaluate the effect of changing Doppler flow pattern on growth and intertwin growth discordance. Methods: This was a retrospective cohort study of all Type‐III sFGR pregnancies managed at nine fetal centers over a 12‐year time period. Higher‐order multiple pregnancy and cases with major fetal anomaly or other monochorionicity‐related complications at presentation were excluded. Estimated fetal weight (EFW) was assessed on ultrasound for each twin pair at five timepoints (16–20, 21–24, 25–28, 29–32 and > 32 weeks' gestation) and compared with singleton and uncomplicated monochorionic twin EFW. EFW and intertwin EFW discordance were compared between pregnancies with normalization of umbilical artery Doppler of the smaller twin later in pregnancy and those with persistently abnormal Doppler. Results: Overall, 328 pregnancies (656 fetuses) met the study criteria. In Type‐III sFGR, the smaller twin had a lower EFW than an average singleton fetus (EFW Z ‐score ranging from −1.52 at 16 weeks to −2.69 at 36 weeks) and an average monochorionic twin in uncomplicated pregnancy ( Z ‐score ranging from −1.73 at 16 weeks to −1.49 at 36 weeks) throughout the entire gestation, while the larger twin had a higher EFW than an average singleton fetus until 22 weeks' gestation and was similar in EFW to an average uncomplicated monochorionic twin throughout gestation. As pregnancy advanced, growth velocity of both twins decreased, with the larger twin remaining appropriately grown and the smaller twin becoming more growth restricted. Intertwin EFW discordance remained stable throughout gestation. On multivariable longitudinal modeling, normalization of fetal umbilical artery Doppler was associated with better growth of the smaller twin ( P  = 0.002) but not the larger twin ( P  = 0.1), without affecting the intertwin growth discordance ( P  = 0.09). Conclusions: Abnormal fetal growth of the smaller twin in Type‐III sFGR was evident early in pregnancy, while EFW of the larger twin remained normal throughout gestation. Normalization of umbilical artery Doppler was associated with improved fetal growth of the smaller twin. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Patrones de crecimiento del embarazo de gemelos monocoriónico complicado por una restricción selectiva del crecimiento fetal de tipo III Objetivos: Se conoce poco sobre los patrones de crecimiento fetal en el embarazo de gemelos monocoriónico complicado por la restricción selectiva del crecimiento fetal (RSCF) de tipo III. El objetivo de este estudio fue evaluar el crecimiento fetal y el patrón Doppler de la arteria umbilical en el RSCF tipo III a lo largo de la gestación y evaluar el efecto del cambio del patrón de flujo Doppler en el crecimiento y la discordancia del crecimiento de los gemelos . Métodos: Este fue un estudio de cohorte retrospectivo de todos los embarazos con RSCF de tipo III tratados en nueve centros fetales durante un período de 12 años. Se excluyeron los casos de embarazo múltiple de alto orden o con anomalías fetales importantes u otras complicaciones relacionadas con la monocorionicidad en el cuadro clínico inicial. Se evaluó el peso estimado del feto (PEF) en la ecografía de cada par de gemelos en cinco momentos (16–20, 21–24, 25–28, 29–32 y >32 semanas de gestación) y se comparó con el PEF de gemelos monocoriales sin complicaciones. Más tarde en el embarazo se comparó la discordancia del PEF y el PEF entre gemelos entre los embarazos con Doppler normal de la arteria umbilical del gemelo más pequeño y aquellos con Doppler persistentemente anómalo . Resultados: En total, 328 embarazos (656 fetos) cumplían los criterios del estudio. En el RSCF de tipo III, el gemelo más pequeño tuvo un PEF inferior al de un feto único medio (intervalo de la puntuación estándar de PEF entre ‐1, 52 a 16 semanas y ‐2, 69 a 36 semanas) y al de un gemelo monocoriónico medio en un embarazo sin complicaciones (intervalo de la puntuación estándar entre ‐1, 73 a 16 semanas y ‐1, 49 a 36 semanas) en toda la gestación, mientras que el gemelo de mayor tamaño tuvo un PEF superior al de un feto medio monocoriónico hasta las 22 semanas de gestación y fue similar en PEF al de un gemelo monocoriónico medio sin complicaciones en toda la gestación. A medida que avanzó el embarazo, la velocidad de crecimiento de ambos gemelos disminuyó, permaneciendo el gemelo más grande con un crecimiento adecuado y el gemelo más pequeño con una mayor restricción de crecimiento. La discordancia del PEF entre gemelos se mantuvo estable a lo largo de la gestación. En la modelización longitudinal multivariable, la normalización del Doppler de la arteria umbilical fetal se asoció con un mejor crecimiento del gemelo más pequeño (P=0, 002) pero no del gemelo más grande (P=0, 1), sin afectar a la discordancia de crecimiento entre gemelos (P=0, 09) . Conclusiones: El crecimiento fetal anómalo del gemelo más pequeño en casos de RSCF de tipo III fue evidente desde el principio del embarazo, mientras que el PEF del gemelo más grande se mantuvo normal durante toda la gestación. La normalización del Doppler de la arteria umbilical se asoció a una mejora del crecimiento fetal del gemelo más pequeño . 摘要: 单绒毛膜双胎妊娠合并III型选择性胎儿生长受限的生长模式 目标: 关于单绒毛膜双胎妊娠合并 III 型选择性胎儿生长受限 (sFGR) 的胎儿生长模式知之甚少。我们旨在评估妊娠期 III 型型选择性胎儿生长受限(sFGR) 中的胎儿生长和脐动脉多普勒模式，并评估 改变多普勒血流模式对生长 和双胞胎间的生长不一致的影响。 方法 : 这是一项回顾性队列研究，研究对象为 12 年期间在九个胎儿中心治疗的所有 III 型型选择性胎儿生长受限(sFGR)妊娠病例。高阶多胎妊娠和出现严重胎儿异常或其他单绒毛膜相关并发症的病例被排除在研究之外。在五个时间点(妊娠 16‐20、21‐24、25‐28、29‐32 和 > 32 周)通过超声评估每对双胞胎的估计胎儿体重(EFW)，并与单胎和简单的单绒毛膜双胞胎 EFW 进行比较。比较了妊娠后期较小双胞胎的正常脐动脉多普勒与持续异常多普勒情况下的估计胎儿体重 和双胞胎之间 估计胎儿体重不一致的情况。 Results: 总体而言，328 例妊娠(656 个胎儿)符合研究标准。在 III 型选择性胎儿生长受限(sFGR)病例中，较小的双胞胎在整个妊娠期间的估计胎儿体重低于平均单胎胎儿(EFW Z 评分范围从 16 周时的 ‐1.52 到 36 周时的 ‐2.69)和正常妊娠中的平均单绒毛膜双胞胎(Z 评分范围 从 16 周时的‐1.73 到 36 周时的‐1.49)，而较大的双胞胎在妊娠 22 周前的 估计胎儿体重高于平均单胎胎儿，并且在整个妊娠期间的 估计胎儿体重与平均未有并发症的单绒毛膜双胞胎相似。随着妊娠的进展，双胞胎的生长速度都有所下降，而双胞胎中较大的一个保持适当的生长，较小的那个生长受到更多限制。双胞胎间估计胎儿体重不一致的程度在整个妊娠期间保持稳定。在多变量纵向建模中，正常化的胎儿脐动脉多普勒与较小双胞胎的更好生长有关(P=0.002)，但与较大双胞胎的生长无关(P=0.1)，且不影响双胞胎生长不一致的情形(P=0.09)。 选择性胎儿生长受限(正常化的脐动脉多普勒与较小双胞胎的胎儿生长改善有关。